Nanofibers in Drug Delivery System - Dawange, Shreya R.; Boraste, Sahebrao S.; Pingale, Prashant L.; Amrutkar, Sunil V. (Asian Journal of Pharmaceutical Research and Development, 2021)
The possible applications of electrospun fibers in drug delivery systems (DDS) are critically examined in this study. Nanofibers are among the most desirable resources in some kind of a variety of scenarios due to their operational capabilities including valuable features for another young generation of resources in energy, climate, even wellness. Because of its possibility to synthesize polymers with specific functions like greater porous design electrospinning was already presented as the most effective technique for fabricating polymer-based nanostructures. Electrospinning has emerged with the most significant challenge for fabricating nanostructures with several advantageous properties which are helpful in a wide range of uses first from the atmosphere to biomedicine. The medicine delivering mechanisms depending upon nanofibers have made significant progress in terms of regulated and sustained release. This analysis summarizes significant advancements within the production of electrospun nanofibers-based rapidly dispersing dosage form using many fibers, therapeutic agents, including entrapment approaches, as an emphasis on mouth administration. The oral cavity became the most discussed mucous membrane location because it would be open or even simple to examine, whereas the others are difficult for the patient and difficult to determine in vivo, according to this study. The drug-loaded nanofibrous structures are described based on their main functions and also the areas for operation.